An Approach to the Paleoceanographic Characteristics of the Sea-Surface at the Western Mediterranean (Balearic Area) during the Pliocene and Gelasian - Francisco Serrano (Geosciences, 2020)
From the study of the planktonic foraminifer assemblages of the sediments of the Ocean Drilling Program (ODP)-Site 975 (Baleares), sea-surface temperature, seasonality and salinity for the Pliocene and Gelasian of the Western Mediterranean were estimated. The estimates were carried out by the modern analog technique (MAT) using PaleoUma, a calibration dataset of 735 North-Atlantic and Mediterranean core-tops. In order to compare Pliocene–Gelasian and present-day analog assemblages, the necessary reduction of the taxonomic variables leads to statistically insignificant increases in estimation error, assessed on the calibration dataset itself. In addition, the correlation with δ18O results as an independent proxy, supports the use of MAT in order to establish the dominant paleoceanographic frameworks during the Pliocene and Gelasian. The SST curve shows an increase trend of the average value since the Early Zanclean (19.7 ± 1.8 °C) to the Late Piacenzian (20.9 ± 1.7 °C) and a decrease until the Late Gelasian (18.1 ± 1.4 °C). The seasonality offers permanently lower estimates than the current value (9.8 °C), reaching the closest values during the Late Gelasian (8.6 ± 0.8 °C). The salinity estimates are overall slightly lower during the Zanclean (36.7‰ ± 0.5‰) than today (37.3‰), whereas they reach up to more than 38.5‰, in the Early Piacenzian. The paleoceanographic frameworks deduced from the combination of the paleoceanographic parameters suggest that the current water-deficit regime in the Mediterranean was clearly predominant throughout the Pliocene and Gelasian. However, since the Piacenzian this regime alternates with stages of water surplus, which are especially frequent in the late Piacenzian. By the middle of the Early Gelasian the regime becomes more predominantly in deficit again.